Is Gangliocytic Paraganglioma Designated as a Subtype of Composite Paragangliomas and Originated From Pancreas Islet? A Case Report and Review of Literature - Li, Jing; Wang, Lu-Ping; Zhu, Pei-Shuang (Frontiers in Endocrinology, 2022)
Gangliocytic paraganglioma (GP) is quite rare, and origin and entity remain to be elucidated. A 51-year-old man presented with GP as a sessile polyp with a smooth surface that measured about 1 cm in diameter in the descending portion of duodenum. Pathological examination displayed that a neoplasm was predominantly located in the submucosa and infiltrated mucosa focally. The tumor consisted of epithelioid, ganglion-like, and spindle cells admixing in a haphazard way. The epithelioid cells resembled paraganglioma in cytological and architectural features. The ganglion-like cells were scattered and merged with the bland spindle cells in fascicular clusters, which resembled ganglioneuroma. Synaptophysin (Syn), microtubule-associated protein-2 (MAP-2), and chromogranin A (CgA) were positive in the epithelioid and ganglion-like cells in variety, and neurofilament (NF) staining highlighted the ganglion-like cells. S-100 and SOX-10 were positive in the spindle cell proliferation and around the epithelioid cells. Progesterone receptor (PR) was positive in the epithelioid cells. The polyp was resected, and no adjuvant therapy was given. The patient remained with no recurrence in 2 years’ follow-up. Origin of GP is presumed to be related to pancreas islet. GP is distinguished from neuroendocrine tumor (NET) G1 and designated as paraganglioma-ganglioneuroma, a kind of composite paragangliomas.